A molecular intravascular ultrasound contrast agent allows detection of activated platelets on the surface of symptomatic human plaques. (December 2017) - Maier, Alexander; Plaza-Heck, Patricia; Meixner, Fabian; Guenther, Felix; Kaufmann, Beat A.; Kramer, Mara; Heidt, Timo; Zirlik, Andreas; Hilgendorf, Ingo; Reinöhl, Jochen; Stachon, Peter; Bronsert, Peter; et al.
Abstract: Background and aims: Activated platelets are amongst the most attractive imaging targets in atherosclerosis due to their important role in early processes of atherogenesis and thrombus formation. We developed a molecular intravascular ultrasound (IVUS) approach to detect activated platelets ex vivo on the surface of human plaques, using an IVUS system applied in clinical routine. Methods: Human carotid endarterectomy specimens were obtained directly from the operating room and exposed to artificial arterial flow conditions for incubation with the contrast agent. This consists of microbubbles (MB), which are linked to an antibody against the ligand induced binding site (LIBS) of the activated platelet glycoprotein IIb/IIa, and a sialyl Lewis polymer (SL), which mediates binding to selectins (LIBS-SL-MB). IVUS was performed pre and post incubation with LIBS-SL-MB and after rinsing with PBS. In comparison, IVUS was performed pre and post incubation with MBs linked to an unspecific control antibody and a dysfunctional polymer (control-MB). All imaging results were correlated to histology findings. Results: IVUS imaging showed a high signal enhancement after administration of LIBS-SL-MB. After rinsing with PBS, the signal enhancement remained stable. Immunofluorescence and immunohistochemistry confirmed significant binding of microbubbles to thrombi on the plaque surface. Moreover, thrombus size and number of bound MBs correlated well. Conclusions: LIBS-SL-MB allows ex vivo IVUS imaging of even small numbers of activated platelets on the surface of human carotid endarterectomy specimens. This diagnostic approach could deliver valuable additional information for risk stratification of atherosclerotic plaques, especially since we apply a clinically well-established IVUS imaging system. Highlights: LIBS-SL-MB allows molecular ex vivo IVUS imaging of activated platelets on the surface of human carotid plaques. Immunofluorescence and immunohistochemistry confirmed significant binding of microbubbles to thrombi on the plaque surface. Thrombus size and number of bound MBs correlated well.